2015
DOI: 10.1093/humrep/dev248
|View full text |Cite
|
Sign up to set email alerts
|

A RCT of psychotherapy in women with nausea and vomiting of pregnancy

Abstract: These findings show that adding 3 weeks of psychological intervention to medical therapy may appear to produce positive therapeutic outcomes upon conclusion of treatment, and 1 month after treatment. This suggests that psychotherapy should be considered as an adjunctive treatment option for women with moderate NVP. In future studies, however, a group of patients who are receiving placebo psychotherapy along with medical treatment should be included. Furthermore, an economic evaluation of the addition of psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
0
17
1
2
Order By: Relevance
“…Four studies evaluated psychological interventions including: CBT (Bittner et al., ; Milgrom et al., ); CBA (Brugha et al., ) and MCBT (Faramarzi et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies evaluated psychological interventions including: CBT (Bittner et al., ; Milgrom et al., ); CBA (Brugha et al., ) and MCBT (Faramarzi et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…One study was assessed to have an overall "low risk of bias" (Faramarzi, Yazdani, & Barat, 2015). One study was assessed as having an overall "high risk of bias" (Korol & Von Baeyer, 1992).…”
Section: Quality Of Randomized Controlled Trialsmentioning
confidence: 99%
“…However, little published evidence on the effects of psychological intervention for HG patients is available. The RCT of Faramarzi et al [24] concluded that psychotherapy added to medical therapy yielded significant improvements in NVP-specific and anxiety/depression symptoms, compared with medical therapy alone among women with NVP. Further research into the efficacy of psychological interventions for HG patients is required.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression play an important role in increased symptoms in women with PMS [13]. Previous studies provide strong support for the efficacy of MBCT for the treatment of depressive/anxiety disorders [28, 48]. As with many applications of mindfulness and related meditation techniques, framing MBCT within a relaxation or stress coping context can play a large role in improving outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have shown that MBCT reduces depression and anxiety in women [28], few studies have examined the effectiveness of MBCT in women with PMS. Bluth et al conducted a pilot study for the effectiveness of MBCT on PMDD.…”
Section: Introductionmentioning
confidence: 99%